Happily ever after representations of gender politics in This Guy’s in Love with U Mare! - Cayabyab, Angeline E. (Plaridel, 2022)
Access online through this link: https://www.plarideljournal.org/article/happily-ever-after-representations-of-gender-politics-in-this-guys-in-love-with-u-mare